The Peculiar Challenges of SMT to African Languages (2013)
The challenges of Machine translation (MT) have been identified and classified but the classification did not consider the peculiarities of African languages. This paper therefore explores the challenges of MT and reclassifies them in relation with the uniqueness of African languages. The study uses the Yoruba language as a template for other African languages and identifies some of the peculiarities of African languages which include Tie fact that they are resource-scarce languages; dycritization, demarcation of discipline, and funding, amongst others. The paper recommends measures to overcome some of these challenges.